PENGARUH INFORMATION TECHNOLOGY RELATEDNESS TERHADAP KINERJA PERUSAHAAN DENGAN KNOWLEDGE MANAGEMENT CAPABILITY SEBAGAI VARIABEL INTERVENING - Mita Ayu Wulandari; Anik Malikah; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThe purpose of this research is to know the influence of informationtechnology relatedness to company performance, and to know influence ofinformation technology relatedness to company performance with knowledgemanagement capability as intervening variable.This research used survey method using primary data obtained from thequestionnaire. Population in this research is private university in Malang withrespondent that is head of information technology department. Selection ofrespondents was done by purposive sampling method. Based on the criteria usedthere are 45 respondents who were sampled. The method used in this research is pathanalysis method.The test results showed that: 1) information technology relatednesssignificantly positive effect on company performance. 2) information technologyrelatedness has a significant positive effect on company performance with knowledgemanagement capability as variable intervening.Keywords: information technology relatedness, knowledge management capability,company performance.